Effectiveness of the expansion of Nagari Situak Ujung Gading, Lembah Malintang District, West Pasaman Regency - Marlina, Siska; Frinaldi, Aldri; Asnil, Asnil; Febrian, Atlis (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Expansion is one of the impacts of the phenomenon of regional autonomy. The movement of expansion of government administrative areas from the top un level to the lowest level, namely villages in the Minang kabau culture in West Sumatra province. The aim is to determine the effectiveness of Expansion and to find out the factors that influence the effectiveness of the Expansion of Nagari Situak Ujung Gading, Lembah Melintang District, West Pasaman Regency. The method in this study uses descriptive qualitative research, namely an analysis that seeks to provide a detailed description based on the facts found in the field regarding the effectiveness of the expansion of Nagari Situak Ujung Gading. The results showed that the effectiveness of the expansion of the Situak Ujung Gading nagari based on the research conclusions was quite effective. Based on the theory of effectiveness by Duncan, it is proven by the many and significant changes in all fields, both social, economic, educational and cultural in the Situak Ujung Gading nagari. The influencing factors are human resources, cooperation, facilities and infrastructure and community participation. The existence of regional expansion in nagari Situak Ujung Gading has become a developed and superior nagari through basic training and human resource advancement. training and the advancement of human resources.